San-Huang-Xie-Xin-Tang constituents exert drug-drug interaction of mutual reinforcement at both pharmacodynamics and pharmacokinetic level: a review - Jiasi Wu; Yingfan Hu; Li Xiang; Sheng Li; Yi Yuan; Yi Yuan; Xiaomei Chen; Yan Zhang; Wenge Huang; Xianli Meng; Ping Wang (Frontiers Media S.A., 2016)
Abstract Inflammatory disorders underlie varieties of human diseases. San-huang-xie-xin-tang (SHXXT), composed with Rhizoma Rhei (Rheum palmatum L.), Rhizoma Coptidis (Coptis chinensis Franch), and Radix Scutellaria (Scutellaria baicalensis Georgi), is a famous formula which has been widely used in the fight against inflammatory abnormalities. Mutual reinforcement is one of the basic theories of traditional Chinese medicine. Here this article reviewed and analyzed the recent research on (1) How the main constituents of SHXXT impact on inflammation-associated signaling pathway molecules. (2) The interaction between the main constituents and efflux pumps or intestinal transporters. The goal of this work was to,(1) Provide evidence to support the theory of mutual reinforcement. (2) Clarify the key targets of SHXXT and suggest which targets need further investigation.(3) Give advice for the clinical use of SHXXT to elevated the absorption of main constituents and eventually promote oral bioavailability. We search literatures in scientific databases with key words of 'each main SHXXT constituent', in combination with 'each main inflammatory pathway target molecule' or each main intestinal transporter, respectively. We report the effect of five main constituents on target molecules which lies in three main inflammatory signaling pathways, we as well investigate the interaction between constituents and intestinal transporter.We conclude,(1)The synergistic effect of constituents at both levels confirm the mutual reinforcement theory of TCM as it is proven in this work. (2) The effect of main constituents on downstream targets in nuclear need more further investigation. (3) Drug elevating the absorption of rhein, berberine and baicalein can be employed to promote oral bioavailability of SHXXT.